Dekonstruksi Budaya Patriakhal pada Film Perempuan Berkalung Sorban - Elka Anakotta (Jurnal Kajian Bahasa, Sastra dan Pengajaran (KIBASP), 2020)
This study aims to deconstruct patriarchal culture by using the film Perempuan Berkalung Sorban, through the binary opposition of patriarchal culture built, by reversing the binary opposition. Film content in the world of pesantrem is very thick with patriarchal cunlture that fences it, and the deconstruction of this culture is done both by the main characters namely Anisa, Khudori (Anisa husband), Anisa’s mother, and some female students who in many ways oppose culture that places women as inferior, weak, and dependent to men. Anisa’s deperate efforts despite having to return to “prison” became never ending struggle because there will still many who opposed what she did. Keywords: Decontruction, Patriarkhal cultural, The Film Perempuan Berkalung Sorban